Correlation analysis of serum AAG/LDH and BLa levels with the prognosis of severe pneumonia complicated with shock: Serum AAG/LDH and BLa levels in severe pneumonia with shock - Yang, Jie; Li, Jia; Tang, Feng; Wu, Mengjuan; Wang, Zhiqiang; Song, Ziqi (Journal of Medical Biochemistry, 2026)
Objective This study aimed to explore the relationships between serum α1-acid glycoprotein (AAG), lactate dehydrogenase (LDH), and blood lactate (BLa) levels and the severity and prognosis of severe pneumonia (SP) complicated with shock in elderly patients to provide useful references for clinical diagnosis and treatment. Methods From May 2024 to July 2025, 364 elderly patients with SP combined with shock who were admitted to our hospital composed the SP combined with shock group. Depending on their severity, the patients were split into low-, medium-, and high-risk groupings. A good prognosis group and a bad prognosis group were subsequently assigned to the patients based on the follow-up data. An additional 364 elderly patients with SP who did not experience shock and were admitted to our hospital during that time frame were chosen to be part of the SP group. Following measurements of each research participant’s serum levels of AAG, LDH, and BLa, the AAG/LDH ratio was calculated. APACHE II (Acute Physiology and Chronic Health Evaluation II) and CPIS (clinical pulmonary infection) scores, and the AAG, LDH, and BLa levels of elderly patients with SP combined with shock were correlated with each other using Spearman correlation analysis. Using multivariate logistic regression analysis, the factors influencing the progression to high risk and poor prognosis in elderly patients with SP accompanied with shock were investigated. A receiver operating characteristic (ROC) curve was used to assess the predictive power of serum AAG/LDH and BLa for the prognosis of elderly individuals with SP accompanied with shock. Results While the SP group’s serum LDH level was lower than the SP group’s, the SP combined with shock group’s serum AAG and BLa levels and AAG/LDH ratios were higher. Each of these variations was statistically significant (P<0.05). The low-risk category had 120 patients, the medium-risk subgroup had 158, and the high-risk segment had 86. While the low-risk subgroup’s serum LDH level was higher than that of the medium-risk and high-risk subgroups (P<0.05), the low-risk subgroup’s serum AAG levels, BLa levels, AAG/LDH ratios, APACHE II scores, and CPIS scores were lower. The medium-risk subgroup’s blood AAG, BLa, AAG/LDH ratio, APACHE II score, and CPIS score were all lower than the high-risk subgroup’s, but the high-risk subgroup’s serum LDH level was greater (P<0.05). Spearman correlation analysis revealed a negative correlation (P<0.05) between the serum LDH level and the APACHE II score and CPIS score, and a positive correlation (P<0.05) between the serum AAG level, BLa level, AAG/LDH ratio, and APACHE II score in elderly patients with SP and shock. There were 94 patients with poor prognoses and 270 patients in the group with good prognoses. While the good prognosis group had a greater serum LDH level than the bad prognosis group, the good prognosis group had lower serum AAG and BLa levels, a lower AAG/LDH ratio, a lower APACHE II score, and a lower CPIS score (P<0.05). Multivariate logistic regression analysis showed that elevated blood AAG/LDH and BLa levels were independent risk variables for progression to high risk and poor prognosis in elderly SP combined with shock patients (P<0.05). In predicting poor prognosis in older patients with SP and shock, the areas under the curve (AUCs) for blood AAG/LDH and BLa were 0.841 and 0.823, respectively, according to the results of the ROC curve study. When predicting poor outcome in elderly patients with SP and shock, the combined AUC of AAG/LDH and BLa was 0.934, higher than the AUC of each sign alone (P<0.05). Conclusion In elderly patients with SP complicated by shock, the levels of serum AAG/LDH and BLa show abnormal changes, which are closely related to the severity of the disease and patient prognosis. The combination of serum AAG/LDH and BLa for predicting the prognosis of elderly patients with SP complicated by shock has relatively high value.